The influence of training load on postural control and countermovement jump responses in rugby union - Troester, C. J.; Jasmin, G. J.; Duffield, R. (Science and Medicine in Football, 2019)
Purpose: This study investigated responses of single-leg balance and landing and countermovement jump (CMJ) following rugby union training and the specific components of training load associated with test decrement.